Association Between Breakfast and Dysmenorrhea in Female College Students at Faculty of Medicine, Pelita Harapan University - Agnes, Agnes; Rivami, Dwi Savitri (Medicinus, 2024)
Background: Breakfast is an activity of eating and drinking that usually takes place after waking up until 9 A.M. and can fulfill 20-25% of daily nutritional needs. Unsupervised skipping breakfast can affect women's ovarian and uterus dysfunction. Dysmenorrhea is one of the diseases that can reduce productivity and quality of life in women. Previous studies have found a high incidence of dysmenorrhea in female college students who didn't have breakfast. Currently, there isn't much data regarding the association between breakfast and dysmenorrhea in female college students in Indonesia.Aim: The aim of this study is to discover the association between breakfast and dysmenorrhea in female college students of Faculty of Medicine at Pelita Harapan University.Methodology: This study is an unpaired analytical comparative categoric design study with a cross-sectional method. Data was collected from 60 college students of Faculty of Medicine at Pelita Harapan University using breakfast questionnaire, WaLLID score for dysmenorrhea, IPAQ-SF and PSS-10 were used to control the confounding variables. The data was analyzed using SPSS 23.Results: Among 60 samples were collected, the majority of female college students didn't have breakfast habit by 55%. There are 76.7% of female students who suffer dysmenorrhea, 91.7% have moderate and severe stress levels, 85% have high physical activity, and 70% of female college students have normal nutritional status. The results of the analysis showed that the p value > 0.05 for the association between breakfast with dysmenorrhea.Conclusion: There is no significant association between breakfast and dysmenorrhea.